Services offshoring and wages: evidence from micro data - Ingo Geishecker; Holger Görg (Institute for the Study of Labor (IZA), 2008)
This paper investigates the effects of services offshoring on wages using individual level data combined with industry information on offshoring. Our results show that services offshoring affects the real wage of low and medium skilled individuals negatively. By contrast, skilled workers benefit from services offshoring in terms of higher real wages. Hence, offshoring has contributed to a widening of the wage gap between skilled and less skilled workers. This result is obtained while controlling for individual and sectoral observed and unobserved heterogeneity. In particular, our empirical model also controls for the impact of technological change and offshoring of materials.
urn:nbn:de:101:1-2008072325
Keywords: F16; 330; Services offshoring; individual wages; Dienstleistungssektor; Unternehmensdienstleistung; Offshoring; Auslandsproduktion; Lohnstruktur; Qualifikation; Dienstleistung; Import; Großbritannien